Integrasi Media Wordwall dalam Meningkatkan Kemampuan Kognitif Anak Usia 5-6 Tahun - Ahmad Aly Syukron Aziz Al Mubarok; Tasya Ayu Damayanti (Amaliyatu Tadris (AMYTA), 2026)
This study strengthens contemporary classroom action research (CAR) by integrating Wordwall-based digital game learning to improve early childhood cognitive skills. The state of the art shows that most previous studies examined Wordwall effectiveness using quasi-experimental designs, leaving a gap in iterative reflective classroom improvement models. This research employed the Kemmis and McTaggart CAR model in two cycles involving 30 children aged 5-6 years at RA Al-A’yun Mojokerto. Data were collected through observation, interviews, and documentation and analyzed using mastery percentage. The results indicate a substantial increase from 33.3% (pre-cycle) to 90% (cycle II). The conceptual contribution of this study lies in proposing a digital-reflective PTK model suitable for PAUD in the post-pandemic learning era. The findings imply that structured integration of educational games within CAR cycles can significantly enhance cognitive engagement and number concept mastery